Percutaneous coronary intervention of the left main coronary artery bifurcation: Insights from the PROGRESS-BIFURCATION registry - Carvalho P. E.; Strepkos D.; Alexandrou M.; Mutlu D.; Rempakos A.; Jalli S.; Kultursay B.; Karagoz A.; Krestyaninov O.; Khelimskii D.; et al. (My University, 2025)
Background: There is limited data on the long-term outcomes of percutaneous coronary intervention (PCI) in patients with left main coronary artery (LM) bifurcation lesions. Methods: This observational, cohort study was performed across 6 centers in the United States, Russia, and Turkey between 2013 and 2024, as part of the Prospective Global Registry of Percutaneous Coronary Intervention in Bifurcation Lesions (PROGRESS-BIFURCATION, NCT05100992). We examined procedural characteristics and follow-up outcomes of patients with versus without LM bifurcation lesions undergoing PCI. Multivariable adjusted hazard ratios (aHR) with 95 % confidence intervals [CI] were calculated using mixed effects Cox regression. Results: Of 1171 patients who underwent bifurcation PCI, 308 (26.3 %) underwent LM PCI. Patients in the LM group were older (76.3 ± 11.0 vs 65.5 ± 11.5 years; p < 0.001) and had more comorbidities, such as diabetes, heart failure, prior PCI, and prior coronary artery bypass graft surgery. Two-stent techniques were more commonly used in LM vs. non-LM patients (38.7 % vs 26.2 %, p < 0.001), with similar technical (95.6 % vs 94.8 %, p = 0.56) and procedural (90.6 % vs 91.1 %; p = 0.796) success. Side-branch occlusion was less common in LM patients (4.0 % vs 16.9 %, p < 0.001). During a median follow-up period of 1095 days, LM bifurcation PCI patients had higher incidence of major adverse cardiac events (MACE) (aHR 1.91; 95 % CI 1.42–2.56;p < 0.001) and all-cause mortality (aHR 2.29; 95 % CI 1.55–3.41; p < 0.001) compared with non-LM bifurcation PCI patients. There was no difference between groups in the incidence of other individual components of MACE. Conclusion: Compared with patients undergoing non-LM bifurcation those who underwent LM bifurcation PCI were older, had more comorbidities, similar procedural success but higher follow-up MACE and mortality.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Kalp Ve Kalp Damar Sistemleri; Clinical Medicine (Med); Clinical Medicine; Cardiac & Cardiovascular Systems; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; bifurcation; left main coronary artery; percutaneous coronary intervention